2013
DOI: 10.1120/jacmp.v14i5.4335
|View full text |Cite
|
Sign up to set email alerts
|

Gemstone spectral imaging: determination of CT to ED conversion curves for radiotherapy treatment planning

Abstract: The monochromatic images acquired by Gemstone spectral imaging (GSI) mode on the GE CT750 HD theoretically determines the computed tomography (CT) number more accurately than that of conventional scanner. Using the former, the CT number is calculated from (synthesized) monoenergetic X‐ray data. We reasoned that the monochromatic image might be applied to radiotherapy treatment planning (RTP) to calculate dose distribution more accurately. Our goal here was to provide CT to electron density (ED) conversion curv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 29 publications
(51 reference statements)
1
26
0
Order By: Relevance
“…The GSI dual-energy CT system has shown promise in diagnostic imaging for patients with orthopedic prostheses (Lee et al , 2012), spinal screws (Wang et al , 2013), and fiducial markers (Brook et al , 2012). Although there has been some interest in using GSI dual-energy CT for radiation therapy treatment planning (Yagi et al , 2013), no studies to the authors' knowledge have to date performed a thorough evaluation of this dual-energy CT system as an artifact mitigation method for treatment planning purposes.…”
Section: Introductionmentioning
confidence: 99%
“…The GSI dual-energy CT system has shown promise in diagnostic imaging for patients with orthopedic prostheses (Lee et al , 2012), spinal screws (Wang et al , 2013), and fiducial markers (Brook et al , 2012). Although there has been some interest in using GSI dual-energy CT for radiation therapy treatment planning (Yagi et al , 2013), no studies to the authors' knowledge have to date performed a thorough evaluation of this dual-energy CT system as an artifact mitigation method for treatment planning purposes.…”
Section: Introductionmentioning
confidence: 99%
“…5 Another approach to metal artifact reduction is the use of dual-energy CT. Dual-energy CT has many applications for diagnostic imaging, [6][7][8] but few studies have looked at its use for treatment planning. [9][10][11] One such dual-energy CT system, GE Healthcare's Discovery CT750 HD (Milwaukee, WI), acquires dual-energy projection data via fast kilovoltage switching with a single x-ray source. This dual-energy projection data can then be reconstructed to generate virtual monochromatic images at various energy levels (from 40 to 140 keV), called gemstone spectral imaging ().…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we first demonstrated that the WDI could relieve the effect of the contrast‐enhancing agent on dose distributions better than the VMI at 77 keV, which provided the equivalent HU values with the conventional SECT image . The effect of iodine on dose distribution was larger in the TP VMI than that in the TP WDI , and the effect was more prominent when the doses were calculated by more sophisticated dose calculation algorithms.…”
Section: Discussionmentioning
confidence: 84%
“…In this study, we first demonstrated that the WDI could relieve the effect of the contrast-enhancing agent on dose distributions better than the VMI at 77 keV, which provided the equivalent HU values with the conventional SECT image. [15][16][17] The effect of iodine on dose distribution was larger in the TP VMI than that in the TP WDI , and the effect was more prominent when the doses were calculated by more sophisticated dose calculation algorithms. For clinical cases, the difference in the dosimetric parameter between the TP WDI and the TP VMI was significantly larger when the doses were calculated by using more sophisticated dose calculation algorithms.…”
Section: Discussionmentioning
confidence: 99%